The Interaction of miRNA-5p and miRNA-3p with the mRNAs of Orthologous Genes - Yurikova, Oxana; Labeit, Siegfried (Molecular biology, 2019)
miRNAs regulate the expression of many genes and are involved in the development of diseases. We studied miRNAs that interact partly or fully complementarily with the 5'UTR, CDS and 3'UTR of mRNAs of target genes. The MirTarget program used in this study allows for the discovery of miRNA binding sites (BS) in the entire nucleotide sequence of the mRNA and for determining the characteristics of the interactions of miRNAs with mRNAs. We identified five pairs of fully complementary BS for miR-127-5p and miR-127-3p, miR-136-5p and miR-136-3p, miR-431-5p and miR-431-3p, miR-432-5p and miR-432-3p, and miR-433-5p and miR-433-3p in the CDS of the human and animal mRNA of RTL1 gene. The fully complementary BS for miR-6720-5p, miR-6720-3p were identified in the CDS of the FOXF2 gene; BS for miR-3187-5p, miR-3187-3p were found in the CDS of the PLPPR3 gene; BS for miR-4665-5p, miR-4665-3p were found in the 5′UTR of the KIAA2026 gene; BS for miR-135a-5p, miR-135a-3p were found in the 3′UTR of the GLYCTK gene; BS for miR-7106-5p, miR-7106-3p were found in the 3′UTR of the CCDC42B gene. The miRNA-5p and miRNA-3p associated with the RTL1 gene have BS in the mRNAs of 32 target human genes. The miRNA-5p and miRNA-3p associated with the FOXF2, PLPPR3, KIAA2026, GLYCTK and CCDC42B genes have BS in the mRNAs of 27 target genes, involved in development of several diseases. Nucleotide sequences of miRNA-5p and miRNA-3p and BS are conserved over tens of millions of years of divergence of the studied animal species. Binding characteristics of miR-3120-3p and miR-3120-5p, miR-196b-3p and miR-196b-5p, miR-125a-3p and miR-125a-3p, let-7e-3p and let-7e-5p, miR-99b-3p in fully complementary BS of non-coding DMN3OS, HOXA10-AS, SPACA6P-AS genes have been established.